Growth And Survival Rate Red Rili Shrimp (Neocaridina Var Rili) With Different Media Temperature Manipulation - Dimas Satya Parikesit; Iskandar Putra; Niken Ayu Pamukas; Rendi Ginanjar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
One of the obligation biotic component in aquascape are decomposition creature that is shrimp. Red Lili Shrimp is one of the main comodity of ornamental fish with high economic value which grow along with the aquascape bussiness in Indonesia. Until today, the demand of Red Lili Shrimp are very high but the stock is still low, which caused by the influence of temperature in mortality of shrimp. This research objectivity is to knowing the growth and survival rate of Red Lili Shrimp (Neocaridina heteropoda var rili) with temperature manipulation by the treatment 'different media temperature manipulation'. The methode which used in this research was Complete Random Stake 1 factor with 4 times different treatment and 3 times repetition. PO shrimp control maintained in temperature 27 - 29ᴼC, P1 : Treatment 1 the shrimp maintained by temperature 26°± 0,5ᴼC ,P2 : Treatment 2 the shrimp maintained by temperature 29°± 0,5ᴼC ,P3 : Treatment 3 the shrimp maintained by temperature 32°± 0,5ᴼC. By manipulation of temperature given serious effect to absolute growth of weight and survival rate, by giving best temperature in treatment 26 ± 0,5ᴼC by daily growth 8,46 %, the absolute growth is 0,024 gram, the absolute length growth 0,24 cm and survival rate 73 %.Keyword: Manipulasi suhu, Neocaridina heteropoda var Rili, Pertumbuhan ,Kelulushidupan